The Role of the Insular Cortex in Pain - Labrakakis, Charalampos (International journal of molecular sciences, 2023)
The transition from normal to chronic pain is believed to involve alterations in several brain areas that participate in the perception of pain. These plastic changes are then responsible for aberrant pain perception and comorbidities. The insular cortex is consistently found activated in pain studies of normal and chronic pain patients. Functional changes in the insula contribute to chronic pain; however, the complex mechanisms by which the insula is involved in pain perception under normal and pathological conditions are still not clear. In this review, an overview of the insular function is provided and findings on its role in pain from human studies are summarized. Recent progress on the role of the insula in pain from preclinical experimental models is reviewed, and the connectivity of the insula with other brain regions is examined to shed new light on the neuronal mechanisms of the insular cortex’s contribution to normal and pathological pain sensation. This review underlines the need for further studies on the mechanisms underlying the involvement of the insula in the chronicity of pain and the expression of comorbid disorders.